THE PROBLEM OF RESEARCH OF KAZAKHSTANI HIGHER EDUCATION SYSTEM - A. Рүстемовa; A. Oкaдa; K. Рүстем (Journal of Oriental Studies, 2019)
The main purpose of the article is to determine the level of research on the problems of the higher education system in Kazakhstan. Higher education, or higher professional education, is the level of vo- cational education following the secondary or vocational education. The system of higher education is one of the factors playing into the level and prospects of economic and social development. Also as it is directly linked to the development strategy of the state, significance of this topic is evident. In studying this topic, we will conduct a historiographical analysis of research done by representatives of various sci- ence spheres who study the system of higher education. In the course of the historiographical analysis, focus features of domestic and foreign researchers in the study of higher education system and its prob- lems were identified. A systematic analysis was made of studies conducted in various fields of science. Results suggest that studies conducted on the education system of Kazakhstan are more focused on re- forms, their implementation and results. Very little attention has been paid to the policy of Kazakhstan’s cooperation with other countries and organizations that are the main initiators of these transformations. Article materials may be useful to every applicant who is interested in the higher education system. Key words: Kazakhstan, higher education, Bologna process, reforms, internationalization.